Exploting benzene´s unknown Mr Hyde character to develop new photochemistry - Papadakis, Raffaello (My University, 2015)
This is a a seminar dealing with the new discoveries on benzene reactivity based on its Mr Hyde character in order to develop new photochemistry.
This is a a seminar dealing with the new discoveries on benzene reactivity based on its Mr Hyde character in order to develop new photochemistry.
Keywords: Química física - Congresos; Organic material